Pusat Pecinta Hewan Mamalia dan Reptil Dengan konsep Metafora Di Jakarta Barat - Deninta Ananda Ikhsani; Harfa Iskandaria; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Pet Center for Mammal and Reptiles lovers is a place that provides a variety of needs and accommodates activities for pet owners, animal lovers and animal lover communities, especially for mammal and reptile animals. West Jakarta is an area with the highest number of pet owners in all of Jakarta, but the facilities available for animal lovers and animal owners are still inadequate and are not yet available in the same area. At this Pet Center all needs are available in one place, such as providing facilities for buying and selling pets, feed and accessories. For the general public who are interested to own a pet, outdoor display is available for direct viewing and interacting with pets. The services that available starting from health services and grooming / salon for pets. In addition, there are also facilities to carry out community activities such as workshops or gatherings. It is hoped that mammal and reptile lovers center will become a place that can accommodate all activities related to animal lovers.The concept used is the Metaphor Concept, this concept can express the shape of the building according to the object as a symbol and imagination of the architect, so as to produce an expressive form of the building and can make people interested through the appearance of the appearance of the building. Keywords: Metaphor, Pet Center, West Jakarta